Whose Governance? IMF Austerities in a Small Island State: The Case of Jamaica - Bissessar, Ann Marie (Journal of Reviews on Global Economics, 2014)
The International Monetary Fund and the World Bank have for a long time embarked on what can be described as a ’trustee’ relationship with countries in the Commonwealth Caribbean. From the latter half of the 1970s, countries such as Trinidad and Tobago, Guyana, Barbados as well as Grenada were ’forced’ because of their chronic need for ’hard’ currency loans to approach the IMF and the World Bank. These loans were accompanied by structural adjustment measures. This paper attempts, for the first time, to evaluate, in the case of Jamaica, whether the measures introduced by the Lending Agencies resulted in some measure of economic growth in the countries under review. The paper then examines the new agreements entered into by these countries and the measures that accompanied them. The overarching argument is that the forces of globalization as well as austerity measures introduced by lending agencies such the IMF and the World Bank prevents rather than encourages small island governments1 to embark on ’national’ development plans and programs. In other words, the primary argument of this paper is that these countries are constrained in their ability to ’govern’ themselves; rather their economic decisions are largely crafted by the forces of globalization and further reinforced by international lending agencies such as the World Bank and the International Monetary Fund.Â